(untitled) - Hurd, Harry L. (Hoboken, N.J., 2007)
The use of periodically correlated (or cyclostationary) processes has become increasingly popular in a range of research areas such as meteorology, climate, communications, economics, and machine diagnostics. Periodically Correlated Random Sequences presents the main ideas of these processes through the use of basic definitions along with motivating, insightful, and illustrative examples. Extensive coverage of key concepts is provided, including second-order theory, Hilbert spaces, Fourier theory, and the spectral theory of harmonizable sequences. The authors also provide a paradigm for nonparametric time series analysis including tests for the presence of PC structures.
Keywords: Spectral theory (Mathematics),Sequences (Mathematics),Correlation (Statistics),Stochastic processes,Lý thuyết Quang phổ,Chuỗi ( toán học ),Tương quan ( thống kê ),Quy trình Stochastic